The Role of The Philosophy of Science in The Development of Student Character Education in High Schools - Anna Damayanti; Jossiselfiah; Siska Wulandari; Syarnubi, Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
Character education is one of the main pillars in shaping a morally upright generation with global competitiveness. The phenomenon of moral degradation and lack of discipline among students has become a serious concern for schools. Therefore, a more fundamental approach is needed through the application of the principles of the philosophy of science in the character education process. According to Jujun S. Suriasumantri, the philosophy of science functions to